Sonia Alda Mejías. La participación indígena en la construcción de la República de Guatemala, S. XIX (Ediciones de la Universidad Autónoma de Madrid, 2000, 285 pgs.) - Gudmundson, Lowell (Revista de historia., 2002)
It presents a very clear and well-documented view on the issue of the indigenous (rather indigenous communities rather than individuals) and how it was addressed and discussed by political and intellectual leaders from Independence to the end of the 19th century. Among the many sources considered and analyzed in detail, the political discussions contained in the newspapers of the time stand out, as well as the parliamentary debates on various bills and agrarian conflicts to be resolved.